OTORITARIANISME DIGITAL DI MASA PANDEMI COVID-19 STUDIKASUS: PENGGUNAAN APLIKASI PEDULILINDUNGI PADA TAHUN 2021 - Muhammad Bimo Anugrah Idris (2023)
This research examines Digital Authoritarianism during the COVID-19 pandemic. The case study in this study looks at the use of the PeduliLindungi application, especially during the COVID-19 pandemic in Indonesia. PeduliLindungi, which is a contact tracing application used to tackle a spread of the COVID-19 virus in society, has experienced a shift from the Heatlh app which was previously a multipurpose application that can be used to do other things. This research method uses a qualitative descriptive method by relying on secondary and primary data. This descriptive descriptive research tries to see and describe problems from various sources to obtain accurate data. To support this, this descriptive research uses interview methods and collects documents to obtain data. This research use digital authoritarianism as main theory to see the phenomena that occur in the PeduliLindungi application. The results indicate that the obligation of using PeduliLindungi application in the society has led to Technology Determinism that occurs in society. PeduliLindungi is not only a health monitoring application but has also become a mass surveillance application due to the absence of filteration carried out by PeduliLindungi. So that PeduliLindungi has finally implemented the characteristics possessed by Digital Authoritarianism, as well as imported technology from authoritarian regime so that Digital Authoritarianism from the PeduliLindungi application is the result of importing Chinese model digital authoritarianism.